Culture of Clostridium pasteurianum in Defined Medium and Growth as a Function of Sulfate Concentration - Mallette, M. F. (1974)
Clostridium pasteurianum strain W-5 was selected as an anaerobe which may be grown from large inocula in defined media with sulfate as its primary sulfur source. Since it is important to keep inocula small in minimizing transfer of sulfur sources, culture conditions were optimized. The medium devised decreased lag period and generation time when compared with other media, but growth could not be induced consistently with 6 × 10(6) cells per ml or less. Addition of trace elements, chelating agents, reducing agents, metabolites, and spent medium from various stages of growth did not stimulate growth from small inocula. Generation time was 85 min on inoculation with 10(7) or more cells per ml taken from young stocks, but the lag period decreased somewhat with larger inocula. On the other hand, generation time and lag period increased with age of the inoculum. The total yield of cells increased when buffer capacity was increased. Growth of C. pasteurianum W-5 was dependent upon sulfate at relatively low sulfate concentrations, and the organism is thus suitable for study of sulfur metabolism. No evidence of a maintenance requirement for sulfate was detected.